Do mycotoxin contaminated diets and yeast cell wall adsorbent affect meat quality of Nellore bulls finished in feedlot? - A short communication - Custódio, L. [UNESP]; Prados, L. F.; Oliveira, I. M. [UNESP]; Resende, F. D. [UNESP]; Pettigrew, J. E.; Yiannikouris, A.; Siqueira, G. R. [UNESP] (Elsevier, 2019)
Ninety-six Nellore bulls (430 ± 13 kg and 24 months) were assigned to a completely randomized block design (2 × 2 factorial arrangement of treatments) to evaluate meat quality. Dietary treatments consisted of natural or exogenous contamination with mycotoxins (Factor 1), with or without yeast cell wall adsorbent (10 g/animal/d; Factor 2). The diets were provided during 97 d. The meat chemical composition was unaffected (P ≥ .37) by the factors and the averages of variables were 74.2% moisture, 22.7% protein, 1.04% ether extract, and 2.10% ash. The L*, a*, b*, E*, C* (P ≥ .11), cooking loss (P ≥ .24) and Warner-Bratzler shear force (P ≥ .17) were also similar among factors. In conclusion, low mycotoxin contamination and yeast cell wall based adsorbent do not affect meat quality of Nellore bulls finished in feedlot.
Keywords: Adsorbent; Aflatoxin; Beef cattle; Cooking losses; Mycotoxin; WBSF